Untold muddy tales: Paleoenvironmental dynamics of a barren mudrock succession from a shallow Permian epeiric sea - Simoes, M. G. [UNESP]; Matos, S. A.; Warren, L. V. [UNESP]; Assine, M. L. [UNESP]; Riccomini, C.; Bondioli, J. G. (Elsevier B.V., 2016)
During the late Paleozoic, the intracratonic Parana Basin, Brazil, in central Gondwanaland, was covered by a huge (>1.600.000 km(2)), shallow and isolated epeiric sea. Within the Permian succession, oxygen deficient fades are commonly recorded in the Mesosaurus-bearing Irati Formation (Cisuralian, Artinskian/Kungurian) and the overlaying Serra Alta Formation (Guadalupian, Wordian/Capitanian). Barren, dark-grey mudstones are the main facies preserved in this last unit, which has usually discouraged extensive and detailed stratigraphical and paleontological investigations. However, exhaustive sedimentological, taphonomic and paleontological surveys in those deposits reveal a dynamic and complex depositonal history. Based on sedimentary fabric, autochthonous to parautochthonous occurrences of shelly benthic invertebrates (bivalves) and the presence/absence of concretion-bearing and phosphate rich layers, we report variations in the oxygen levels of bottom and pore waters, in bathymetry, sedimentation rates, and changes in benthic colonization. Our data indicate that the deposition of this apparently barren mudstone-dominated succession was driven by a complex interplay of variations in sedimentation rate and oxygen pulses tied to tectonic and climate changes. Three distinct populations or invertebrate paleocommunities were recorded, which were adapted to (a) normal background lowoxygerr (dysoxic) conditions (i.e., minute infaunal suspension-feeding bivalves associated with the trace fossil Planolites), (b) chemically toxic (anoxic/extreme dysoxic) substrates, including gigantic burrowing bivalves (probable chemosymbiotic taxa), and (c) oxic/dysoxic substrates following short-term bottom disruptions. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Benthic paleocommunities; Chemosymbionts; Exaerobic to dysaerobic substrates